Enhancing Higher Order Thinking Skills Among Elementary Students: A Classroom Action Research on Teaching Fractions - Lucy Asri Purwasi Lucy; Putri Natasya Monalisa Anjelina; Evanni Daniswara Haryono (Universitas Negeri Surabaya, 2024)
The aim of this research is to see how the implementation of HOTS-oriented learning can improve the mathematics learning outcomes of fifth grade elementary school students. The research method used was Classroom Action Research (PTK), with the research subjects being class V.b students at SD Negeri 16 Lubuklinggau, totaling 24 people, consisting of 9 men and 15 women. Data collection techniques use tests, observation and documentation. The data analysis techniques used are qualitative descriptive and quantitative descriptive. This research consists of three cycles and each cycle consists of four stages, namely planning, implementing actions, observing and reflecting. The results of this research show that the mathematics learning outcomes of class V students at SD Negeri 16 Lubuklinggau City have improved through the implementation of HOTS (Higher Order Thinking Skills) oriented learning. This is shown through the students' average scores, during the Pre-Cycle the average Pre-test score obtained by students was 42.91, Cycle 1 the Post-test average score was 53.95, Cycle 2 the Post-test average score was 69.58, Cycle 3 Post-test average score 79.58. Therefore, it can be concluded that the implementation of HOTS-oriented learning can be used as an effort to improve the quality of learning in order to form a higher level of thinking in students.